Genomics of entomopathogenic bacterial endosymbiont species associated with desiccation tolerant entomopathogenic nematode - Mothupi, Boipelo (My University, 2016)
Entomopathogenic nematodes in the genera Heterorhabditis and Steinernema have emerged excellent as non-chemical alternatives for control of insect pest population. They have a specific mutualistic symbioses with bacterial symbionts in the genera Photorhabdus and Xenorhabdus, respectively. Native EPN species that are able to tolerate environmental stress including desiccation are of great interest for application. The aim of this study was to isolate indigenous EPN species from soil samples collected from Brits, North West province in South Africa, and to investigate their ability to tolerate desiccation stress. The second aim was to isolate the bacterial symbiont and sequence, assemble and annotate its whole genomic DNA. Insect baiting technique and White trap method proved useful in the recovery of nematodes from collected soil samples and infected cadaver, respectively. Molecular identification based on the amplification of the 18S rDNA and phylogenetic relationships revealed high affinity of the unknown EPN isolate 10 to Steinernema species and due to variation in evolutionary divergence distance, the unknown isolate was identified as Steinernema spp. isolate 10 . Isolates 35 and 42 revealed high similarity to Heterorhabditis zealandica strain Bartow (accession number: GU174009.1), Heterorhabditis zealandica strain NZH3 (accession number: EF530041.1) and the South African isolate Heterorhabditis zealandica strain SF41 (EU699436.1). Both Steinernema spp. isolate 10 and Heterorhabditis species could tolerate desiccation. Steinernema spp. isolate 10 was tolerant up to 11 days of desiccation exposure in loamy sand and up to 9 days of exposure in river sand, causing 26, 6% and 13, 4% cumulative larval mortality after 96 hours, post resuscitation by rehydration, respectively. Heterorhabditis spp. could tolerate desiccation up to 13 days of exposure and induced 26.6% cumulative larval mortality on both loamy and river sand after 96 hours post resuscitation. Swarming, aggregation, coiling and clumping behavioural characteristics were observed when Steinernema spp. isolate 10 was exposed to desiccation and Heterorhabditis species displayed no similar behavioural characteristics associated with desiccation tolerance. Morphological characteristics of the unknown Steinernema spp. isolate 10 have been described, and the thick cuticle and sheath which are both associated with tolerance to desiccation stress have been noted. The bacterial symbiont was isolated from larval hosts infected with Steinernema spp. isolate 10 and molecular identification through NCBI Blastn based on the 16S rDNA revealed high affinity to Xenorhabdus bacterial species. Phylogenetic relationships and evolutionary divergence estimates 16 revealed genetic variation and the species was identified as Xenorhabdus bacterial isolate. The genome assembly of Xenorhabdus bacterial isolate using CLC Bio revealed a total length of 4, 183, 779 bp with 231 contigs (>=400bp), GC content of 44.7% and N50 of 57,901 bp. Annotation of the assembled genome through NCBI PGAAP annotation pipeline revealed 3,950 genes (3,601 protein coding sequences (CDS) and 266 pseudogenes), 12 rRNAs and 70 tRNAs. RAST annotation revealed 55 of virulence, disease and defense subsystem features which are involved in the pathogenicity of Xenorhabdus bacterial isolate. The ability of EPNs to tolerate environmental stress is highly crucial and one of the determining factors for biocontrol potential and successful application, thus the indigenous desiccation tolerant EPN isolate, Steinernema spp. isolate 10 holds great potential as a biological control agent. The genome sequencing and annotation reveals insight to behavioural and physiological attributes of bacterial symbionts and this study will contribute to the understanding of pathogenicity and evolution of the bacteria–nematode complex.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science. Year: 2016.
Keywords: Insect pests--Biological control; Endosymbiosis